THz Radiation from High-Tc Superconducting Materials and Its Applications - Hangyo, Masanori (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001))
Electromagnetic pulses with a time width of less that 0.5 ps are emitted from high-Tc superconductors (HTSC’s) by exciting with ultrashort optical pulses. The radiation is observed under various states, i.e., current biased, magnetic field applied, and magnetic flux trapped states. The radiation mechanism is ascribed to the ultrafast modulation of the supercurrent, which is brought about by the optical Cooper pair breaking. This new phenomenon is applied to noncontact supercurrent imaging and an optical flux trap memory.